THE DYNAMICS OF WOUND HEALING IN THE TREATMENT WITH THE OINTMENT WITH A DRY EXTRACT OF POTENTILLA - L. P. Lezhnevа; A. M. Temirbulatova; E. F. Stepanova; D. V. Veselova (Кубанский научный медицинский вестник)
Aim. The study was designed for the evaluation of the effect of ointments with dry extracts of potentilla on the dynamics of the healing process of full-thickness skin wounds.Materials and methods. The wound healing activity estimation of the proposed dosage form was conducted on white Wistar rats. The results of macroscopic studies (the area of the wound defect, the state of the scab, the presence of hemorrhage beneath it, the degree of inflammatory processes in the underlying tissues, including deeply located tissue structures, up to the muscle elements) and the results of histological examination were the criterion for evaluating the effectiveness of the wound healing agent. In the course of the experiment, the animals were divided into 4 groups: the main group (treatment with the ointment with a dry extract of potentilla), control group No. 1 (treatment with the ointment base), control group No. 2 (without treatment), and control group No. 3 (treatment with the «Chlorophyllipt» drug.Results. The results of the macroscopic and histological studies made it possible to conclude that the wound healing process in the treatment with the ointment with a dry extract of potentilla had a number of features. The proposed dosage form enhanced the regeneration of the multilayered squamous epithelium, accelerated the maturation of the granulation tissue, and eliminated the inflammation and infiltration in the first days of treatment, which led to a significant reduction in the healing time when it was applied (15-18 days). In the animals of the control groups No. 1 and No. 2, the described processes occurred much more slowly, and inflammatory infiltration persisted almost throughout the entire experiment. The wound surface was healed on the 27-30th day. A lot of common features were noted in the mechanism and timing of wound healing in the treatment with the ointment with a dry extract of potentilla and a reference preparation – «Сhlorophyllipt». Conclusion. The ointment with a dry extract of potentilla significantly speeds up the healing process of full-thickness skin wounds.